Samarra'i, Ibrahim. “Abū Ḥayyān Al-Tawḥīdī’s Al-Ishārāt Al-Ilāhiyyah (The Divine Signs),” Year 5, Issue 21 (Summer 1421 AH/ 2000 CE), Pp. 85-117. - السامرائي, إبراهيم (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2000)
Abū Ḥayyān al-Tawḥīdī’s Al-Ishārāt Al-Ilāhiyyah (The Divine Signs) was published in Egypt and edited by Dr. Abdel Rahman Badawi. It was then published and edited in Lebanon by Dr. Wedad al-Qadi. Its content is categorized within the language of supplication to God, and what it contains of the literature of asceticism and mystical (Sufi) and philosophical glimpses. It contains pages portraying the life and struggle of Abū Ḥayyān, his critique of people, depiction of society, and exploration of the inclinations of human souls. Ibrahim Samarra’i’s article finds that despite the effort made by its editor Dr. Badawi, it is not of adequate mastery of the original Arabic it was penned in, to the extent of sound reprinting of the book. Samarra’i provides his assessment of the edited work and calls for a new corrected edition to be published.